Executive Committee Minutes 2011-03-03 - Academic Senate:::::::::
Academic Calendar Change, Appoint Document Review Committee for URTP, Report with recommendations from FSSP regarding the survey of faculty needs in support of externally funded research and scholarship, Report with recommendations from FSSP regarding the survey of faculty needs in support of externally funded research and scholarship, Revision to the Class Attendance Policy, Two Curriculum changes from Kinesiology